Pendekatan Demonstratif dalam Penguatan Pembelajaran Fiqih di Madrasah Tsanawiyah - Lilis Lismawati (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2024)
This study aims to determine the effectiveness of the demonstration method in learning fiqh for grade VII students at MTs Nurul Islam, identify efforts made to improve the effectiveness of the method, and explore supporting and inhibiting factors in its implementation. This study uses a qualitative approach with data collection techniques through observation, interviews, and documentation. The subjects in this study included the Principal, Fiqh Teacher, and grade VII students. Data analysis techniques used include data reduction, data presentation, and data verification. The results of the study indicate that the application of the demonstration method in learning fiqh at MTs Nurul Islam is very effective. Students not only receive theoretical explanations, but can also directly witness and practice materials such as tayamum, ablution, and prayer, so that learning becomes more concrete and meaningful. Efforts made to improve the effectiveness of this method include an initial explanation of the purpose of the demonstration, mental preparation of students before learning, and reflective discussions after the demonstration. The supporting factors for the implementation of the demonstration method include: learning becomes clearer, more interesting, and applicable; students are more active and find it easier to understand the material; and increased student learning experience. Meanwhile, inhibiting factors come from limited facilities and infrastructure, limited time, and uneven readiness of teachers and students. This study recommends the development of demonstration methods on an ongoing basis with the support of adequate facilities and teacher training.